Quality of Sleep Among Dental Students - GUNTUPALLI, YOSHITA; GANAPATHY, DHANRAJ; SASHANKA, KEERTHI (The journal of contemporary issues in business and government, 2020)
Sleep is very important for the normal functioning of any individual. However, with all the responsibilities we face as students, practitioners, academicians and family members, getting the recommended amount of sleep can be very hard. Insufficient sleep can severely impact the health and well being of an individual and bring down their potential to do work. This has negative effects on both individual and societal levels bringing down the quality as well as life span of useful human resources.The aim of this study is to determine the quality of sleep among dental students in South India.A survey was initiated for a randomly chosen dental student population of 100. A questionnaire was prepared involving questions assessing the sleep quality and all its various aspects. This questionnaire was then circulated to all the participants via online basis. The results obtained from the survey were compiled and analyzed.It was found that 70% of students had unpredictable sleeping patterns. 50% had disturbed sleep. Only 17% students reported that they felt fresh after receiving the recommended 8 hrs of sleep per day. 95% of students stayed up late at night. Sleep latency was found to be around 10 minutes to 1 hour for 85% students. 26% reported that they suffered from nightmares. 56% woke up at night for even the small sounds.This study concludes that dental students have a poor quality of sleep owing to their busy schedules, vast syllabus and loads of clinical and practical work.